Characterization of Early-Stage Alcoholic Liver Disease with Hyperhomocysteinemia and Gut Dysfunction and Associated Immune Response in Alcohol Use Disorder Patients - Vatsalya Vatsalya; Khushboo S. Gala; Ammar Z. Hassan; Jane Frimodig; Maiying Kong; Nachiketa Sinha; Melanie L. Schwandt (Biomedicines, 2020)
Heavy alcohol consumption can cause hyperhomocysteinemia, which could be consequential in the proinflammatory response and worsening of the neurobehavioral domains of alcohol use disorder (AUD), such as alcohol withdrawal. We examined the role of heavy drinking, hyperhomocysteinemia, gut dysfunction and inflammation in early-stage alcoholic liver disease (ALD) in AUD patients. A total of 110 AUD patients without clinical manifestations of liver injury were grouped by the serum homocysteine levels (SHL): normal ≤ 13 µmol/L (Group 1 (Gr.1); n = 80), and elevated > 13 µmol/L (Group 2 (Gr.2), n = 30). A comprehensive metabolic panel, SHL, a nutritional assessment, and drinking history assessed by the timeline followback questionnaire were evaluated. A subset analysis was performed on 47 subjects (Gr.1 n = 27; Gr.2 n = 20) for additional measures: Clinical Institute Withdrawal Assessment for Alcohol (CIWA) score, plasma cytokines (interleukin-1β (IL-1β)), gut dysfunction markers (lipopolysaccharide (LPS), and LPS-binding protein (LBP)); 27% of the AUD patients exhibited hyperhomocysteinemia. SHL was significantly associated (p = 0.034) with heavy drinking days (HDD90). Subset analyses showed that the withdrawal ratings were both clinically and statistically (p = 0.033) elevated and significantly associated with hyperhomocysteinemia (p = 0.016) in Gr.2. LBP, IL1-β, SHL, and HDD90 showed significant cumulative effects (adjusted R2 = 0.627) on withdrawal ratings in Gr.2 subset. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were significantly higher in all Gr.2 patients; AUROC showed a fair level of true positivity for ALT (0.676), and AST (0.686). Il1-β, LBP, SHL, and HDD90 showed significant cumulative effects (adjusted R2 = 0.554) on the elevated ALT in Gr.2 subset as well. The gut-brain derived proinflammatory response, patterns of heavy drinking, and hyperhomocysteinemia were closely associated with clinically elevated alcohol withdrawal and elevated liver injury. Hyperhomocysteinemia could have a potential phenotypic marker response indicative of early-stage ALD along with AUD.